IMPROVING EARLY CHILDHOOD COUNTING ABILITY THROUGH MODIFICATION OF ILLUSTRATED COUNTING BOOKS - Desniarti Desniarti; Muhammad Hafiz; Yuan Anisa (SENSEI RESEARCH CENTER, 2022)
Based on law no. 2 of 2003 concerning the national education system where early childhood education needs stimulation to assist physical and spiritual growth and development in entering further education. One of them is by stimulating children's cognitive development by counting early. In this case, one of the efforts that can be made by teachers is to modify the textbooks given to early childhood by providing lots of interesting pictures and colors so that children will be more interested in learning and will understand more about counting. This type of research is Classroom Action Research (CAR) and is carried out on TK-B students with a total of 26 students. Data collection techniques are observation, interviews, documentation, data analysis, data presentation, data interpretation, and reflection in the form of qualitative descriptive research with indicators used, namely sorting numbers 1-15, counting pictures, and rewriting numbers according to the modification of the illustrated textbook that has been designed. The research was conducted in two cycles where each cycle consisted of three meetings. In cycle 1, it has not reached the optimal indicator limit, which is below 75% for all materials. However, in cycle 2, the success indicators have been set so that the researchers stopped this research in cycle 2. Where the success rate for sorting numbers 1-15 has reached 77%, counting images has reached 84.6% and rewriting numbers has reached 92.3. %. and rewrite the numbers according to the modification of the illustrated textbook that has been designed. The research was conducted in two cycles where each cycle consisted of three meetings. In cycle 1, it has not reached the optimal indicator limit, which is below 75% for all materials. However, in cycle 2, the success indicators have been set so that the researchers stopped this research in cycle 2. Where the success rate for sorting numbers 1-15 has reached 77%, counting images has reached 84.6% and rewriting numbers has reached 92.3. %. and rewrite the numbers according to the modification of the illustrated textbook that has been designed. The research was conducted in two cycles where each cycle consisted of three meetings. In cycle 1, it has not reached the optimal indicator limit, which is below 75% for all materials. However, in cycle 2, the success indicators have been set so that the researchers stopped this research in cycle 2. Where the success rate for sorting numbers 1-15 has reached 77%, counting images has reached 84.6% and rewriting numbers has reached 92.3. %. In cycle 1, it has not reached the optimal indicator limit, which is below 75% for all materials. However, in cycle 2, the success indicators have been set so that the researchers stopped this research in cycle 2. Where the success rate for sorting numbers 1-15 has reached 77%, counting images has reached 84.6% and rewriting numbers has reached 92.3. %. In cycle 1, it has not reached the optimal indicator limit, which is below 75% for all materials. However, in cycle 2, the success indicators have been set so that the researchers stopped this research in cycle 2. Where the success rate for sorting numbers 1-15 has reached 77%, counting images has reached 84.6% and rewriting numbers has reached 92.3. %.